2020
DOI: 10.1111/are.14503
|View full text |Cite
|
Sign up to set email alerts
|

The role of açaí ( Euterpe oleracea Mart. 1824) as a chemoprotective agent in the evaluation of antioxidant defence, oxidative damage and histology of juvenile shrimp Litopenaeus vannamei (BOONE, 1931) exposed to ammonia

Abstract: This study investigated the effects of the use of the inclusion of açaí on the diet of shrimp Litopenaeus vannamei on antioxidant and histopathological responses after exposure to ammonia. The shrimps were fed two experimental diets: control and with 10% of açaí inclusion (W/W), for 35 days. Afterwards, the organisms were exposed at four concentrations of ammonia (0.01‐control; 0.26; 0.48 and 0.91 mg NH3‐N L−1) for 96 hr. The total antioxidant capacity (ACAP) of the gills decreased significantly in both diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…In turn, reductions in the content of P‐SH groups in shrimp exposed to 10 μl L −1 EOC for 6 h imply a pro‐oxidant scenario. A study by Colombo et al (2020) showed that shrimp fed with açai and exposed to non‐ionized ammonia (NH 3 ) had decreased concentrations of P‐SH in their gills and muscle. Thus, the presence of P‐SH is related to the maintenance and protection of the redox state of proteins, while the depletion of P‐SH demonstrates protein carbonylation (Fedorova et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, reductions in the content of P‐SH groups in shrimp exposed to 10 μl L −1 EOC for 6 h imply a pro‐oxidant scenario. A study by Colombo et al (2020) showed that shrimp fed with açai and exposed to non‐ionized ammonia (NH 3 ) had decreased concentrations of P‐SH in their gills and muscle. Thus, the presence of P‐SH is related to the maintenance and protection of the redox state of proteins, while the depletion of P‐SH demonstrates protein carbonylation (Fedorova et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several antioxidant compounds and bioactive molecules from plants have been used as dietary supplements or in immersion baths as they improve immune and antioxidant defence systems in fish and crustaceans (Colombo et al, 2020; He et al, 2017; Parodi et al, 2012; Reverter et al, 2014; Saccol et al, 2016; Sarangarajan et al, 2017; Souza et al, 2017). The use of EOs as sedatives or anaesthetics can improve the antioxidant capacity of shrimp (Akbari et al, 2010; Parodi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In intensive production systems, ammonia concentrations might rise quickly and become toxic, representing a high risk for the reared organisms. Shrimps under increased ammonia-N concentration can present impaired antioxidant capacity, with loss in compensatory antioxidant mechanisms that can cause a severe oxidative stress condition (Romano and Zeng, 2013;Colombo et al, 2020;Wang et al, 2020). Also, nitrite is a toxic nitrogen waste that can induce not only lethal responses in the shrimp Litopenaeus vannamei (Ramírez-Rochin et al, 2017) but also affects its gut microbiota, favoring pathogens like Pseudoalteromonadaceae and Vibrionaceae (Huang et al, 2020).…”
Section: /10mentioning
confidence: 99%
“…Stressful conditions are commonly observed in superintensive production systems (Gao et al, 2017;Souza et al, 2019) as elevated ammonia concentration can promote the generation of reactive oxygen species (ROS) (Ray et al, 2012;Colombo et al, 2020). ROS induction in aquatic animals occurs under unfavorable biochemical and physiological conditions, such as pH, temperature and toxins (Kütter et al, 2014;Birnie-Gauvin et al, 2017).…”
Section: /10mentioning
confidence: 99%
See 1 more Smart Citation